ACETONIDES OF ALPHA-HYDROXY-DELTA-ALTRONOLACTONES - Bichard, C; Fairbanks, A; Fleet, G; Ramsden, N; Vogt, K; Doherty, O; Pearce, L; Watkin, D (1991)
The preparation and characterisation of some derivatives of α-hydroxy-δ-lactones, in which the δ-carbon substituent on the lactone ring is trans to an adjacent isopropylidene protected diol, are described; the X-ray crystal structures of 3,4-O-isopropylidene-D-altrono-1,5-lactone and of 3,4:6,7-di-O-isopropylidene-D-glycero-D-altro-heptono-1,5-lactone are reported. © 1991.